2002
DOI: 10.1002/jnr.10136
|View full text |Cite
|
Sign up to set email alerts
|

Plasma melatonin, pinealocyte morphology, and surface receptors/antigen expression on macrophages/microglia in the pineal gland following a high‐altitude exposure

Abstract: The present study examined the effects of high-altitude exposure on the pineal gland, the main source of production of melatonin. It was surmised that hypoxia experienced at high altitude, caused by decreased oxygen tension in the ambient air, might lead to some structural alterations in the pineal gland and, hence, affect its melatonin production. Adult Wistar rats were exposed to an altitude of 8,000 m for 2 hr in an altitude chamber and then sacrificed at various time intervals after the exposure. Normal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…This activation could be due to a direct effect of melatonin on the microglial cells, as it has been reported that administration of exogenous melatonin upregulates the immune responses (Maestroni et al, 1988). Recently, Kaur et al (2002) have shown that the upregulation of CR3 and MHC II antigen on the microglial cells were coincident with the peak plasma levels of melatonin after altitude exposure. Our study (Ananth et al, 2003b) offers the possibility of potential therapeutic use of melatonin for the prevention of DA-induced neuronal damage.…”
Section: Neuroprotective Role Of Melatonin In Da-induced Neurotoxicitymentioning
confidence: 96%
“…This activation could be due to a direct effect of melatonin on the microglial cells, as it has been reported that administration of exogenous melatonin upregulates the immune responses (Maestroni et al, 1988). Recently, Kaur et al (2002) have shown that the upregulation of CR3 and MHC II antigen on the microglial cells were coincident with the peak plasma levels of melatonin after altitude exposure. Our study (Ananth et al, 2003b) offers the possibility of potential therapeutic use of melatonin for the prevention of DA-induced neuronal damage.…”
Section: Neuroprotective Role Of Melatonin In Da-induced Neurotoxicitymentioning
confidence: 96%
“…For example, hypoxia temporarily increases circulating levels of melatonin. Melatonin generally leads to increased immune function, especially in laboratory rodents (Frisch et al, 2004;Kaur et al, 2002). Similarly, hypoxia positively influences circulating levels of leptin, a hormone known to be a positive regulator of the immune system (Bernotiene et al, 2006;Fantuzzi and Faggioni, 2000;Grosfeld et al, 2002;Meissner et al, 2005;Shukla et al, 2005).…”
mentioning
confidence: 99%
“…176,177 Hypoxia exposure of Wistar rats steadily increased plasma melatonin activity to a plateau at seven days. 178 To what extent the beneficial actions of IHT in AD are due to increased release of melatonin by the pineal gland remains to be determined.…”
mentioning
confidence: 99%